(untitled) (Journal of the College of Basic Education, 2023)
The aim of this study to investigate the effect of crude hot aqueous extract of cocoon beetle Larinus maculatus Faldermann(Family: Curculionidae) in a different doses(50,100,200,300)mg/Kg/ day respectively with periods (15,25,35,45) days respectively on some hematological parameters such as hemoglobin(Hb),red blood cells count(RBCs),Packed cell volume(PCV),mean corpuscular volume(MCV),mean corpuscular hemoglobin(MCH),mean corpuscular hemoglobin concentration (MCHC)and white blood cells count(WBCs)were determined in mice Mus musculus administered orally the extract .The results showed that there was a significant decrease (P<0.05) in Hb ,PCV, RBCs values, and MCV,MCH and MCHC also affected by the extract for all of the treatments and in all the periods . In WBCs values there was a significant increase (P<0.05) with all of treatments and with different periods .The results therefore indicate there was anemia with experimental animals and the presence of undesirable effect in the use of aqueous extract of beetle cocoon in the raw form at least at the administered concentrations and for the duration of feeding. The findings are unhealthy since the raw extract of this cocoon is currently being used as drug as treatment for cough, bronchitis in many families in Iraq ,Syria, Turkey and Iran